catena-Poly[[[diiodidomercury(II)]-μ-N,N′-di-3-pyridylpyridine-2,6-dicarboxamide] dimethylformamide solvate] - Huang, Li-Hua (International Union of Crystallography, 2008)
In the title complex, {[HgI(2)(C(17)H(13)N(5)O(2))]·C(3)H(7)NO}(n), the Hg atom is coordinated by two I atoms and two N atoms from two different ligands in a distorted tetrahedral environment. Hg atoms are bridged by N,N′-di-3-pyridylpyridine-2,6-dicarboxamide ligands, forming a helical chain running along the a axis.